Positive Solutions for Boundary Value Problems of Fractional Differential Equation with Integral Boundary Conditions. (22nd April 2018) - Sun, Qiao; Ji, Hongwei; Cui, Yujun
Abstract : By using two fixed-point theorems on cone, we discuss the existence results of positive solutions for the following boundary value problem of fractional differential equation with integral boundary conditions:D 0 + α x ( t ) + a ( t ) f ( t, x ( t ) ) = 0, t ∈ ( 0, 1 ), x ( 0 ) = x ′ ( 0 ) = 0, andx ( 1 ) = ∫ 0 1 x ( t ) d A ( t ) .